Integration in home care, effects on worker stress - Timo Sinervo; Sanna Laulainen; Joakim Zitting; Salla Lehtoaro; Vuokko Niiranen; Laura Hietapakka; Ilmo Keskimäki (International Journal of Integrated Care, 2019)
Introduction: Elderly care and especially home care has severe challenges in Finland. As home care has become more dominant in elderly care and clients are more dependent work has become most stressful. The proportion of people over 75 years in institutional has decreased clearly and proportion of people in home care has increased, but the number of personnel in home care has not increased accordingly. Some areas have already organized the services under joint authorities, acting like planned counties. Organizing all services under same management has opened several new possibilities to integrate services, as one answer to the problems in home care. The aim of this study is to analyze care integration and it’s effects in three organizations. Methods: Our data were gathered from three areas of about 150000 inhabitants in each. Two of the areas had established a joint authority of health and social care (one 8 years ago, second one year ago), third one was planning the new organization. We are using a mixed method approach with personnel survey (N=1943, in elderly care N=403)  and interview data (46 employees or managers from elderly care and 17 top managers). Relationships between well-being and care integration is analyzed with variance analysis, and inductive content analysis interview data. Results: All organizations were developing case management. Two organizations had developed co-operation between hospital and home care (discharge process). The organization with longest history had several ways of integration. Rehabilitation was moved from institutions to home rehabilitation and numerous physiotherapists were working in home care. Also co-operation between home care, hospital emergency and outpatient care had been developed. Small acute care unit of paramedics was visiting elderly patient in case of acute condition. With contact to GP (using ICT-services) patient’s transfer to emergency care or hospital admission could be avoided in many cases. Despite the promising examples there was no clear relationship with integration and employee well-being in interviews. Employees felt that elderly people living at home are in too bad condition and they are discharged from hospital too early, despite the strong effort on home rehabilitation. In the questionnaire data, however, better co-operation and information flow with all sectors of health and social care was related to lower time pressure. Discussion and conclusion: There are promising novel ways to integrate elderly care to rehabilitation and emergency care as well as developing case management. However, these developments seem to have effect on worker well-being only limitedly in workers experiences in qualitative analyses. In quantitative analyses better interaction with elderly care and other sectors was related to lower stress, in terms of time pressure. Limitations: We had three large organizations in our study. All organizations were in different phases of their development, which may affect our results.